The path to parity: exploring the lived experiences of first-at-institution female community college presidents - Madore, Brenda K. (Kansas State University, 2024)
This qualitative hermeneutic phenomenological study explores the lived experiences of first-at-institution female community college presidents in the United States, focusing on the social influences they encountered. Despite community colleges serving a large number of female, underrepresented, and low-socioeconomic students, leadership roles are predominantly held by White males. Data from the American Council on Education and the American Association of Community Colleges reveal a slow increase in female representation in these roles, but progress has stagnated since 2010. This study echoes the importance of representation in leadership, and historical sentiments about power and identification. Using Interpretive Phenomenological Analysis (IPA), it delves into the lived experiences of these female leaders to uncover the contextual factors that influenced their journeys as viewed through the lens of social capital theory. Findings reveal that attaining the presidency came at a high personal cost. Love emerged as both the motivation and intrinsic reward for these leaders. Broad experience and knowledge were identified as crucial factors for achieving such positions. Additionally, a supportive spouse had a significant positive impact on some journeys. Authenticity was deemed essential, and female friendships provided important emotional and social support. Moreover, males in power were critical advocates for these female presidents. Based on these findings and by understanding the experiences of these female leaders and the contextual factors that impacted them, valuable insights can be provided for boards of trustees, aspiring presidents from underrepresented groups, and those interested in achieving parity in community college presidencies. This study may encourage prospective female leaders to seek the presidency and informs stakeholders about the critical support systems needed to foster diversity in leadership.
Keywords: Lived experiences; Female community college presidents; Interpretive Phenomenological Analysis (IPA); Social capital theory; Diversity in leadership